Thermal stability of the functional ingredients, glucosylated benzophenones and xanthones of honeybush (Cyclopia genistoides), in an aqueous model solution. (15th October 2017) - Beelders, Theresa; de Beer, Dalene; Ferreira, Daneel; Kidd, Martin; Joubert, Elizabeth
Highlights: Addition of 3′-OH to 3- β -d -glucopyranosyliriflophenone decreased stability. Glucosylation of 3- β -d -glucopyranosyliriflophenone at 4-OH enhanced stability. 3- β -d -Glucopyranosylmaclurin cyclised to form mangiferin and isomangiferin. Position of sugar moiety affects xanthone stability. Xanthones were more stable than their benzophenone precursor. Abstract: Thermal stability of the benzophenones, 3- β -d -glucopyranosyl-4- β -d -glucopyranosyloxyiriflophenone (1 ), 3- β -d -glucopyranosylmaclurin (2 ) and 3- β -d -glucopyranosyliriflophenone (3 ), and the xanthones, mangiferin (4 ) and isomangiferin (5 ), was assessed separately in an aqueous model solution (pH 5) to delineate their major degradation products and mechanism(s). Degradation followed first-order reaction kinetics and the temperature-dependence of the respective reaction rate constants complied with the Arrhenius equation. The stability of the compounds increased in the order2  > 4  > 3  > 5  > 1 . 4- O -Glucosylation significantly stabilised1 against degradation compared to3, enediol B-ring functionality of2 decreased stability compared to3 and position of glucosylation affected the stability of the xanthones with5 being more stable than4 . The xanthone nucleus (C-ring) conferred higher stability to4 and5 compared to their benzophenone analogue2 . Cyclisation of2 to4 and5 would underestimate their degradation in mixtures. Other reactions were isomerisation, dimerisation, acetylation and hydrolysis.